An emerging zoonotic disease to be concerned about - a review of the nipah virus - Sumit Paliwal; Suneet Shinu; Rubina Saha (Journal of Health, Population and Nutrition)
Abstract The Nipah Virus (NiV) was discovered in 1999 in the Sungai Nipah region of Malaysia. It is one of many emerging bat-borne zoonotic viruses that threaten global health security. The Pteropus fruit bats are identified as the natural reservoirs for the virus. NiV belongs to the family of Paramyxoviridae and is mostly present in locations surrounded by water, vegetation, and controlled or protected religious areas. To date, cases of NiV have been identified in Southeast Asian regions, with the highest number of cases in Bangladesh, totalling 305, with a fatality rate of 65%. The highest mortality has been observed in the Indian region, at 73%. NiV is an emerging zoonotic disease that needs to be focused on. The median incubation period is 9.5 days and the clinical features primarily lead to either progressive encephalitis or Acute Respiratory Distress Syndrome. The diagnosis is conducted in Bio-safety level 3 or level 4 labs through Polymerase chain reaction. Human nasal swabs, throat swabs, urine, blood, and cerebrospinal fluid (CSF) are collected for diagnostic purposes. At present, there is no approved treatment or vaccine for the prevention of the disease. However, research on a vaccine against NiV is being investigated, and a subunit vaccine with NiV-G protein is found to produce potential efficacy. An outbreak in Kerala, a state in India, led to the implementation of an action plan involving lead agencies to combat the sudden surge of the virus. In the current scenario, appropriate preventive strategies are more effective in controlling the virus. However, emphasis should be placed on affordable and efficient diagnostic methods, treatment options, and vaccines to better manage the virus, considering the highest fatality caused by the virus.